PEMAHAMAN MAHASISWA TERHADAP KURIKULUM EKONOMI 1994 SEKOLAH MENENGAH UMUM - Suyanto Suyanto (Universitas Negeri Yogyakarta, 1999)
Abstract The purpose of this study is to investigate students’ understanding of 1994 high school economics curriculum. The problems of this study are formulated as follows: (1) What economics curriculum materials are difficult to understand?; (2)What curriculum concepts or materials are difficult to teach when students would assume teaching position after they graduated? This exploratory study utilizing survey design has been done in the Department of Cooperative Economics, Faculty of Social Studies Teaching, Institute of Teaching and Educational Sciences Yogyakarta. The sample of this study is drawn by using convenient sampling technique. From this technique, eighty seven students can be determine as the sample in this study. This sample consists of those students who are in the 3rd, 5th, and 7th semester. Data analysis is done with univariate and bivariate descriptive method by using SPSS computer software. The finding of this study are: (1) students’ understanding in 1994 high school economics curriculum generally are low both in terms of teaching context and in terms of economics structure; (2) Curriculum materials which are the most difficult to understand and also difficult to teach, are the ones of the third quarter of the third grade of economics high school classes. Those materials consist of (1) Simple Linear Regression; (2) The Application of Regression in Economics; (3) Time Series (4) The analysis of Time Series Data; (5) Linear Secular Trend: (6) The Use of Time Series Analysis in Economics. Those difficulties arise because the majority of students do not fully master the concept themselves and the method how to teach those concepts. Keywords:1994 economics curriculum; high school; cooperative economics